2013
DOI: 10.1177/1071100712467434
|View full text |Cite
|
Sign up to set email alerts
|

Flouroscopic Arthrography Versus MR Arthrography of the Lesser Metatarsophalangeal Joints for the Detection of Tears of the Plantar Plate and Joint Capsule

Abstract: Level II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Cadaveric studies have shown improved visualization of articular structures in the first and lesser MTPJs using dMRA compared with cMRI at 1.5 T [ 372 374 ]. Clinical studies have also suggested utility of dMRA for demonstrating capsular and plantar plate tears in the lesser MTPJs [ 375 377 ], though there is a paucity of head-to-head studies in comparison with cMRI. As there is often a joint effusion and/or synovitis present which provides most of the diagnostic benefits of dMRA without the invasive procedure [ 378 , 379 ], many authors emphasize high-quality cMRI exams with dedicated surface coils rather than dMRA [ 378 381 ].…”
Section: Hipmentioning
confidence: 99%
“…Cadaveric studies have shown improved visualization of articular structures in the first and lesser MTPJs using dMRA compared with cMRI at 1.5 T [ 372 374 ]. Clinical studies have also suggested utility of dMRA for demonstrating capsular and plantar plate tears in the lesser MTPJs [ 375 377 ], though there is a paucity of head-to-head studies in comparison with cMRI. As there is often a joint effusion and/or synovitis present which provides most of the diagnostic benefits of dMRA without the invasive procedure [ 378 , 379 ], many authors emphasize high-quality cMRI exams with dedicated surface coils rather than dMRA [ 378 381 ].…”
Section: Hipmentioning
confidence: 99%
“…Although plain radiographs are usually sufficient to diagnose sesamoid fractures and dislocations, magnetic resonance imaging can aid assessment of the associated ligamentous, capsular, and plantar plate injuries which need surgical repair to avoid instability and postoperative pain [7] , [8] , [9] . Also MR arthrography claimed to be the best in identification of plantar plate and capsular tears of the first metatarsophalangeal joint [10] , [11] . Trikha et al reported a similar case of type one dislocation with failed closed reduction as the inersesamoid ligament was tense and required release of the deep transverse ligament [12] .…”
Section: Discussionmentioning
confidence: 99%